KELENGKAPAN DATA KARAKTERISTIK KARTU PENDERITA KUSTA DI PUSKESMAS KRAMATSARI DAN PUSKESMAS DUKUH DI KOTA PEKALONGAN PERIODE JANUARI 2017 SAMPAI 2019 - Dianita Desti Kartikasari; Atik Mawarni; Sri Winarni; Dharminto Dharminto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Leprosy is a chronic infectious disease caused by Mycobacterium Leprae which attacks peripheral nerves and other body tissues. To determine the status of elimination of leprosy, it required the completeness, accuracy and punctuality of the records, where the results would be reported in stages, it would be needed in leprosy card. In 2018, the prevalence rate in Pekalongan City has reached 2.39 per 10,000 cases which can’t be stated free from leprosy. The purpose of this study was to determine the characteristic data completeness of leprosy card at Kramatsari and Dukuh Public Health Centers in Pekalongan City in January 2017 until 2019. The type of this research is descriptive. The population of this research are all of the leprosy cards in all public health centers in Pekalongan City from January 2017 to 2019 as many as 127 leprosy cards with the sample size of this research are 32 leprosy cards. The samples were selected by using purposive sampling with inclusion criteria. The data was analyze using univariate analysis. The results showed that the percentage of leprosy card completeness at Kramatsari and Dukuh Health Centers was 21.9% while the incompleted was 78.1%. The percentage of leprosy card completeness based on age, gender, type of work, history of illness, abnormalities and disability is 31.25% while the percentage of leprosy card completeness based on treatment is only 21.9%.